'It's about keeping children safe, not spying': A governmentality approach to Prevent in primary education. (May 2022) - da Silva, Raquel; Fontana, Giuditta; Armstrong, Megan A
From its inception in 2015, the Prevent Duty has required educators, and other members of the social sector, to exercise 'due regard' in preventing pupils from being drawn into terrorism, irrespective of the age of the child. This article explores how primary educators have understood and implemented this preventative security policy in their schools. Analysis is based on a survey of 345 primary school educators and 37 semi-structured interviews with primary school educators and Prevent Education Officers from the West Midlands. Through a lens of governmentality, we shed light on how this mandate has been broadly interpreted and exercised by educators within and outside the school gates. In so doing, we contribute to debates on the puzzling acceptance of Prevent in education, on the process whereby educators identify threats, and on the securitisation of educational spaces in a risk society.